Angiolymphatic invasion as a prognostic fator in resected N0 pancreatic adenocarcinoma - ALMEIDA,Ricardo Vitor Silva de (2017)
ABSTRACT Background: Pancreatic adenocarcinoma remains one of the worst digestive cancers. Surgical resection is the main target when treating a patient with curative intent. Aim: To assess angiolymphatic invasion as a prognostic factor in resected pN0 pancreatic cancer. Methods: Thirty-eight patients were submitted to pancreatoduodenectomy due to head pancreatic cancer. Tumor size, margins, lymph nodes, pTNM staging, angiolymphatic and perineural invasion were described in the pathologists' reports. Results: Most patients were female. Overall median survival was 13 months. Gemcitabine was the regimen of choice for chemotherapy in selected patients; however, it did not improve overall survival. pR0 resection had better survival compared with pR1. Within the pN0 group, survival was significantly better in patients without angiolymphatic invasion. Conclusion: Angiolymphatic invasion in N0 pancreatoduodenectomy can be demonstrated by the Hematoxylin-Eosin stain and may predict a poor prognosis factor for those patients.